Umbilical Cord-Derived Mesenchymal Stem Cells Ameliorate Nephrocyte Injury and Proteinuria in a Diabetic Nephropathy Rat Model - Lian Chen; E. Xiang; Changyong Li; Bing Han; Quan Zhang; Wei Rao; Cuihong Xiao; Dongcheng Wu (Journal of Diabetes Research)
Mesenchymal stem cells (MSCs) are shown to alleviate renal injury of diabetic nephropathy (DN) in rats. However, the underlying mechanism of this beneficial effect is not fully understood. The aims of this study are to evaluate effects of umbilical cord-derived mesenchymal stem cells (UC-MSCs) on renal cell apoptosis in streptozotocin- (STZ-) induced diabetic rats and explore the underlying mechanisms. Characteristics of UC-MSCs were identified by flow cytometry and differentiation capability. Six weeks after DN induction by STZ injection in Sprague-Dawley rats, the DN rats received UC-MSCs once a week for consecutive two weeks. DN-related physical and biochemical parameters were measured at 2 weeks after UC-MSC infusion. Renal histological changes were also assessed. Moreover, the apoptosis of renal cells and expression of apoptosis-related proteins were evaluated. Compared with DN rats, rats treated with UC-MSCs showed suppressed increase in 24-hour urinary total protein, urinary albumin to creatinine ratio, serum creatinine, and blood urea nitrogen. UC-MSC treatment ameliorated pathological abnormalities in the kidney of DN rats as evidenced by H&E, PAS, and Masson Trichrome staining. Furthermore, UC-MSC treatment reduced apoptosis of renal cells in DN rats. UC-MSCs promoted expression of antiapoptosis protein Bcl-xl and suppressed expression of high mobility group protein B1 (HMGB1) in the kidney of DN rats. Most importantly, UC-MSCs suppressed upregulation of thioredoxin-interacting protein (TXNIP), downregulation of thioredoxin 1 (TRX1), and activation of apoptosis signal-regulating kinase 1 (ASK1) and P38 MAPK in the kidney of DN rats. Our results suggest that UC-MSCs could alleviate nephrocyte injury and albuminuria of DN rats through their antiapoptotic property. The protective effects of UC-MSCs may be mediated by inhibiting TXNIP upregulation in part.